Audit Committee Independence and Voluntary Disclosure: Evidence from Listed Manufacturing Companies in Nigeria (Journal of Management and Social Sciences, 2024)
This study investigated the influence of audit independence on voluntary disclosure of listed manufacturing companies in Nigeria from the period of 2015-2019. Purposive sampling technique was used to include all the thirty-three (33) manufacturingcompanies (both Industrial and Consumer Goods) listed on the Nigerian Stock Exchange. Information was generated using content analysis of annual reports. A disclosure check list consisting of fifty items was developed based on relevant previousstudies and Nigeria Code of Corporate Governance (NCCG)’s principles. Static panel data (Pooled OLS, panel Fixed Effect Model, panel Random Effect Model), correlation matrix and descriptive statistics were employed in the estimation. The estimation of the static panel model shows that audit committee independence has positive impact on the level of voluntary information disclosed. It was concluded that the level of companies’ voluntary disclosure of information is hinged on the extent of dependence of its audit committee. The study recommended the need for functional and independent audit committee, which will aid in minimizing agency and monitoring costs. In order to ensure the independence of audit committee, the chairman of the board of directors or managing director or chief executive officer nor any of the executive directors should be memberof audit committee that there is need for functional and independent audit committee.